The study of impact response of composite material - Mohd Alfaduly, Mohamad Saleh (2008)
Composite materials have been increasingly used in automotive engineering, aerospace development, marine technology, electronic devices, and construction industries. This paper highlights a computational model to analyze the behavior of composite material subjected to impact load tensile load. General purposed commercial finite element code was employed to develop the computational model. Fiber glass reinforced composite, one of the commonly used structural composites, was chosen for the test material. Computational model was constructed 2-D axis-symmetric finite elements. Elastic-plastic material model was incorporated into the finite element modeling to reflect material purpose under impact load and relevant material properties were taken from the published report. In order to account for high strain rate effect, load was applied at the nodes of one end while the other end of the model was constrained. Linear Static Stress was then performed to predict deformation and damage zone. For comparison purpose, impact tensile test was carried out the load and the specimen size as close as possible to those used in computational model. Both computational and experimental results are found to be in good agreement in terms of damage size.